Unlocking innovation in the sport industry through additive manufacturing - Meier, M.; Tan, K.H.; Lim, M.K.; Chung, L. (Emerald, 2018)
Fast changing customer demands and rising requirements in product performance constantly challenge sports equipment manufacturers to come up with new and improved products to stay competitive. Additive Manufacturing (AM), also referred to as 3D Printing, can enhance the development of new products by providing an efficient approach of rapid prototyping. This research aims to analyse the current adoption of AM technologies in the innovation process of the sports industry i.e. level of awareness; how it is implemented; and it impact on the innovation process. Literature research shows that AM brings many possibilities to enhance the innovation process, and case studies indicated several obstacles that hinder the technology from fully unfolding. AM is still at the early stage of entering the sports equipment industry and its potential benefits have not been fully exploited yet. The findings generated from the research of real life practices show that AM provides several benefits when it comes to the innovation process, such as a faster development process, an optimised output, as well as the possibility to create new designs. However, companies are not yet able to enhance the innovation process in a way that leads to new products and new markets with AM. Limitations, including a small range of process able material and an inefficient mass production, still restrain the technology and lead to unused capability. Nevertheless, future prospects indicate the growing importance of AM in the innovation process and show that its advancement paves the way to new and innovative products.